2011
DOI: 10.1590/s0104-42302011000500022
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos nutricionais na lesão renal aguda

Abstract: Nutritional assessment is an indispensable tool for the evaluation and clinical monitoring of patients with acute kidney injury (AKI). Acute loss of renal function interferes with the metabolism of all macronutrients, responsible for proinflammatory, pro-oxidative and hypercatabolic situations. The major nutritional disorders in AKI patients are hypercatabolism, hyperglycemia, and hypertriglyceridemia. Those added to the contributions of the underlying disease, complications, and the need for renal replacement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
12

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 30 publications
0
6
0
12
Order By: Relevance
“…This suggests that the fatal cases might have had more severe envenomation. Because albumin is a relatively slow-reacting negative acute-phase reactant it may be associated with higher mortality in AKI[35]. Hypoalbuminemia was as result of a generalized increase in capillary permeability and bleeding complications.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the fatal cases might have had more severe envenomation. Because albumin is a relatively slow-reacting negative acute-phase reactant it may be associated with higher mortality in AKI[35]. Hypoalbuminemia was as result of a generalized increase in capillary permeability and bleeding complications.…”
Section: Discussionmentioning
confidence: 99%
“…It was regarded as not only a marker of inflammation or malnutrition [810], but also a risk factor of AKI development and mortality in critically ill patients [6, 1114]. A meta-analysis of observational studies showed that the odds of AKI and death among patients with AKI increase by 134% (pooled odds ratio [OR], 2.34; 95% confidence interval [CI], 1.74–3.14) and 147% (pooled OR, 2.47; 95% CI, 1.51–4.05), respectively, with each 10 g L -1 serum albumin decrement [6].…”
Section: Introductionmentioning
confidence: 99%
“…Perforated pneumatosis cystoides intestinalis, caused by infection with a gas-producing bacterium, is thought to be the most common cause of spontaneous pneumoperitoneum in adults without perforation [10] , [11] . In adults, pneumatosis cystoides is considered to be idiopathic or secondary to chronic medical conditions [12] .…”
Section: Discussionmentioning
confidence: 99%